Plasma Exchange is a Therapeutic Procedure used in the Management of Rapidly Progressive Glomerulonephritis (RPGN): A Case Report - Chekmat, Muh. Dina Tursina; Pratiningrum, Dwi Lestari; Lestariningsih, Lestariningsih; Arwanto, Arwedi; Chasani, Shofa; Nurani, Ayudyah; Setiawan, Budi; Miranti, Ika Pawitra (Newinera Publisher, 2026)
Rapidly Progressive Glomerulonephritis (RPGN) is a clinical syndrome characterized by a rapid decline in kidney function and the presence of crescents on kidney biopsy, requiring immediate treatment to prevent disease progression. A 34-year-old man was admitted to the hospital with generalized body swelling that began in the eyelids one week prior. He had a history of fever before admission, which subsided upon hospitalization. Additional complaints included shortness of breath, cough, and runny nose. Past medical history included hypertension and hiperuresemia. In recent days, he experienced oliguria. Physical examination revealed pitting edema in the lower extremities. Laboratory tests showed anemia, hypoalbuminemia, and rapid decline in kidney function. Urinalysis revealed protein +3, leukocytes sediment 80.1/µL, erythrocytes sediment 468/µL, and Esbach 0.5 g/L. Complement C3 53 mg/dL, C4 13.8 mg/dL, ANA, and anti-dsDNA were negative, with no available data for anti-GBM, ANCA and kidney biopsy Segmental Mesangial Hypercellular Glomerulus and focal segmental sclerosis. Chest X-ray showed cardiomegaly, bronchopneumonia, and left pleural effusion. Abdominal ultrasound revealed bilateral parenchymal renal disease. The patient was treated with high dose steroids, antibiotics, antihypertensives, symptomatic medications, two sessions of hemodialysis, and four sessions of plasma exchange (PLEX). The combination therapy of high dose steroids and followed by hemodialysis and plasma exchange, resulted in significant reduction of edema and improvement in kidney function, demonstrating the effectiveness of an aggressive immunomodulatory regimen. In pauci-immune or idiopathic RPGN, the combination of high-dose steroids and plasma exchange along with dialysis provides a rapid clinical response, increases the chance of remission, and preserves kidney function.